Experience in the use of vaccine Gam-Kovid-Vak-M for the prevention of COVID-19 in children - T. M. Chernova; D. O. Ivanov; V. N. Timchenko; S. M. Kharit; M. E. Balakina; Yu. K. Miroshnikova; E. V. Barakina; E. B. Pavlova; A. V. Morozova; N. A. Myskina; I. Yu. Bazunova; A. A. Zherebtsov (Детские инфекции (Москва))
The goal is to evaluate the tolerability and effectiveness of the domestic vector vaccine Gam-Covid-Vak-M in children aged 12—17 years, adherence to vaccination of adolescents and parents to improve work on the prevention of COVID-19. Materials and methods. A retrospective analysis of the medical records of 115 children aged 12—17 years who were vaccinated in 2022 with the Gam-COVID-Vac-M vaccine in two children's polyclinics in St. Petersburg was carried out. Additional information was collected through telephone interviews. A cross-sectional anonymous online survey of adolescents aged 15—17 was also conducted to study awareness of COVID-19 and adherence to vaccination. Results. Only 23.5% of those vaccinated were at risk for severe and complicated COVID-19. Parents showed low adherence to vaccination against COVID-19 — 71.3% vaccinated themselves and 73.1% considered it necessary to protect the child. Only in 14.1% of cases, a teenager aged 15—17 made the decision to be vaccinated. According to 76.9% of adolescents, COVID-19 is a dangerous disease, while 55.6% consider vaccination unnecessary, mainly due to ineffective protection and the possibility of complications. Nevertheless, side effects after the first and second components of Gam-COVID-Vac-M were observed in 24.3% and 24.2%, respectively, which is 4 times less than with foreign vaccines. Systemic and local reactions were observed on days 1—2 after immunization. All manifestations were mild or moderate and resolved within 1—2 days on average. Serious adverse events were not registered. The effectiveness of the vaccine was 97.4%. Conclusion. Preliminary results indicate good tolerance and efficacy of the domestic vaccine Gam-COVID-Vac-M.